Toughening Via Revitrification of Li2SiO3 Crystals in Obsidian. (2022) - Lubauer, J.; Hurle, K.; Cicconi, M.R.; Petschelt, A.; Lohbauer, U.; Belli, R.
Abstract : Purpose/Aim: The aim of this study was to illustrate the microstructural and compositional evolution of a lithium silicate glass-ceramic and to draw conclusions about its mechanical behaviour. Materials and Methods: Blocks of Obsidian (Glidewell Laboratories, USA) were processed into slices measuring 12x12x1.5mm3 for special heat treatment. The heating ramp was interrupted at temperatures between 700 C and 820 C (dwell time at 820 C between 0 min and 10 min) in order to freeze the respective microstructural state. The crystallization peaks of the base and the pre-crystallized glass were detected by DSC. The coefficient of thermal expansion and Tg were derived from DTA. XRD was performed to quantify and characterize the crystal phase fraction, whose microstructural changes were visualised using FE-SEM. The ball on three balls surface crack in flexure method was used to record the development of fracture toughness. Results: The microstructural evolution during crystallization firing revealed the progressive revitrification of the original Li2 SiO3 crystals at the boundaries of nanometric single coherent scattering domains (CSD) starting at 740 C and extending throughout the isothermal stage. The crystal fraction decreased monotonically from 41vol.% of 5 m-sized poly-crystals to 35vol.% 0.5m-sized single-crystals, in opposite trend to the CSD sizes. The KIc accompanied the reverse trend of crystallinity, departing from 1.63±0.02 MPa ↔ m at the pre-crystallized stage to 1.84±0.06 MPa↔m after 10 min at 820 C in a sigmoidal shape. Toughening appeared counter-intuitive in view of the decreasing crystal fraction and size, to rather relate to the relaxation of the residual stresses in the interstitial glass, as let suggest from the disappearance of the extensive microcracking. During heat-treatment, the CTE decreased from 13.7×10-6 K-1 to 12.8×10-6 K-1. Conclusions: Toughening of Obsidian occurs via revitrification and isotropization of Li2 SiO3 crystals and consequent relaxation of anisotropic mismatch in coefficient of thermal expansion between crystal and glass, despite decrease in crystallinity and crystal size.